The diversity of root fungi associated with Erica species occurring in the Albany Centre of Endemism - Bizabani, Christine (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2015)
South Africa has the highest species diversity of ericaceous plants belonging to the Erica genus. There are over 850 identified species in the Cape Floral Region. The Albany Centre of Endemism (ACOE) is located within this region and is a hotspot of diversity consisting of various plant genera. The success of Erica plants is ubiquitously attributed to mycorrhizal relationships they engage in with a diverse group of fungi. This symbiosis is known as the ericoid mycorrhizal (ERM) association. The overall aim of this study was to establish the diversity of root fungi associated with Erica plants using morphological, molecular and 454 pyrosequencing techniques. Six Erica species were identified using leaf and flower morphology according to taxonomic keys. The identified plants were Erica cerinthoides, Erica demissa, Erica chamissonis, Erica glumiflora, Erica caffra and Erica nemorosa. Roots from sampled plants were stained and examined microscopically to determine their mycorrhizal status. Ericoid mycorrhizal associations together with dark septate endophyte (DSE) structures and hyphae that did not form any specific structure were observed in all the roots. In addition arbuscular mycorrhizal (AM) structures in the form of vesicles were detected in E. glumiflora and E. cerinthoides. In order to identify the culturable fungi associated with the respective hosts, sterilised roots were placed on various culture media for cultivation. Thereafter isolated fungi were morphologically classified into 67 morphotypes. These were mostly sterile and darkly pigmented. Non-sporulating mycelia of variable colouration such as white, cream-yellowish, beige, green and brown were also observed. Further identification was carried out using molecular techniques. DNA was extracted separately from pure cultures and amplified using ITS1 and ITS4 primers in a polymerase chain reaction (PCR). Thereafter sequencing and Basic Local Alignment Search Tool (BLAST) were used to identify the isolates to generic level. The fungi were taxonomically classified into 54 operational taxonomic units and 94 percent were Ascomycetes and Helotiales was the dominant order. Unclassified Helotiales with affinities to fungi currently identified as Epacrid root fungus was common in all hosts. Other isolates that were identified included Oidiodendron, Meliniomyces, Phialocephala, Cadophora, Lachnum, Leohumicola Cryptosporiopsis, Chaetomium, Acremonium and Epicoccum species. Basidiomycetes were represented by two OTUs belonging to the genus Mycena. Four OTUs comprised fungi that had no significant alignments in the reference databases. Direct root DNA extraction together with 454 pyrosequencing was used to detect the diversity of culturable and unculturable fungi associated with the identified hosts. The ITS2 region was targeted for sequencing. Although Ascomycetes remained the dominant phyla, Basidiomycetes were also detected in all host plants. Glomeromycota was present in E. caffra and E. cerinthoides. Helotiales was dominant in all Erica plants with the exception of E. cerinthoides and E. chamissonis which were dominated by the order Chaetothyriales. The OTUs identified to genus level included Epacris pulchella root fungus, Oidiodendron cf. maius, Acremonium implicatum, Leohumicola, Lachnum, Capronia and Mycena species. Culture-based techniques and pyrosequencing detected similar fungal composition comprising Ascomycetes, while, pyrosequencing was able to detect Glomeromycetes and Basidiomycetes.
Keywords: Ericaceae; Ericas; Roots (Botany) -- Diseases and pests; Mycorrhizal fungi; Polymerase chain reaction; Fungi -- Classification